2017
DOI: 10.1038/nm.4308
|View full text |Cite
|
Sign up to set email alerts
|

VISTA is an inhibitory immune checkpoint that is increased after ipilimumab therapy in patients with prostate cancer

Abstract: To date, anti-CTLA-4 (ipilimumab) or anti-PD-1 (nivolumab) monotherapy has not demonstrated significant clinical benefit in patients with prostate cancer. To identify additional immune inhibitory pathways in the prostate tumor microenvironment, we evaluated untreated and ipilimumab-treated tumors from patients on a pre-surgical clinical trial. PD-L1 and VISTA inhibitory molecules increased on independent subsets of macrophages. Our data suggest that VISTA is another compensatory inhibitory pathway in prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
383
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(394 citation statements)
references
References 19 publications
10
383
0
1
Order By: Relevance
“…Indeed, we found that breast tumors infiltrated with TIM-3+ iTILs highly correlate with tumors positive for other checkpoint markers (PD-1, PD-L1 and LAG-3). Results are consistent with other reported studies and imply that the expression of multiple different immune checkpoints can occur during tumor progression, reflecting an ongoing battle between cancer cells and the immune system 38,39 . In our cohort, coexpression of TIM-3 with PD-1 and LAG-3 is associated with a particularly favorable prognosis, perhaps reflecting an underlying robust immune recognition of the cancer cells that is difficult for the tumor to evade.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, we found that breast tumors infiltrated with TIM-3+ iTILs highly correlate with tumors positive for other checkpoint markers (PD-1, PD-L1 and LAG-3). Results are consistent with other reported studies and imply that the expression of multiple different immune checkpoints can occur during tumor progression, reflecting an ongoing battle between cancer cells and the immune system 38,39 . In our cohort, coexpression of TIM-3 with PD-1 and LAG-3 is associated with a particularly favorable prognosis, perhaps reflecting an underlying robust immune recognition of the cancer cells that is difficult for the tumor to evade.…”
Section: Discussionsupporting
confidence: 92%
“…Accumulating evidence suggests resistance to anti- CTLA-4 or anti-PD-1/PD-L1 inhibitors can occur in otherwise immunogenic cancers through compensatory upregulation of additional immune checkpoints 39,41 . TIM-3 has recently emerged as a target for cancer immunotherapy following pre-clinical studies suggesting its non-redundant functions in comparison to the better-characterized checkpoint markers PD-1/PD-L1, and efficacious treatment synergy when TIM-3 is targeted in combination with anti-PD1/PDL1 antibodies 26,27,42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, VISTA upregulation after CTLA-4 blockade with ipilimumab was recently reported in prostate carcinomas (32). In this study, VISTA was upregulated in tumor infiltrating immune cells, particularly in CD68+ tumor associated macrophages.…”
Section: Discussionmentioning
confidence: 85%
“…24 In prostate cancer, Gao et al have shown that while ipilimumab increased levels of tumor infiltrating T cells, it also increased levels of other compensatory inhibitory immune checkpoint molecules including PD-L1 and VISTA in tumor specimens from untreated and treated ipilimumab patients in a pre-surgical clinical trial. 25 These observations provide a rationale for combining ipilimumab and nivolumab in patients with prostate cancer, with the goal of targeting …”
Section: Combination Immunotherapy Strategiesmentioning
confidence: 99%